Saint's Progress - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2006)
"Saint's Progress" by John Galsworthy is a novel written in the early 20th century. The story centers around Edward Pierson, a clergyman, who is grappling with personal loss, the responsibilities of fatherhood, and the complexities of love during a turbulent time shaped by war. The opening chapters introduce themes of nostalgia, personal struggle, and the nuances of emerging relationships, particularly focusing on the dynamics between Edward and his daughters. At the start of the novel, Edward Pierson returns from a ramble to the picturesque setting of his brother's home, reflecting on a mixture of beauty and melancholy that surrounds him. The narrative captures his reunion with family, particularly his daughter Noel, as she dances with a young officer. Through Edward's eyes, we see his concern over Noel's growing attachment to Cyril Morland, an officer heading to war. As the story progresses, we witness Edward's internal battle as a father trying to protect his daughter from the potentially reckless choice of marrying someone she has known for a very short time. The opening sets the stage for a heartfelt exploration of love, loss, and the impact of war on intimate relationships. (This is an automatically generated summary.)
Release date is 2006-06-14
Produced by David Widger
Keywords: World War, 1914-1918 -- Fiction